Pierres précieuses – signe contesté de l’Orient dans le Roman d’Eracle de Gautier d’Arras (XIIe siècle) .......... 57 - Dybeł, Katarzyna (Pensées orientale et occidentale : influences et complémentarité II, 2021)
PRECIOUS STONES – A CONTESTED SIGN OF THE EAST IN THE ERACLE ROMANCE OF GAUTIER D’ARRAS (12TH CENTURY)The article analyses the motifs of precious stones present in the 12th century work of Gautier d’Arras, The Eracle Romance (ca. 1176-1184), often called “Byzantine romance”. This motif shows the influence of the Byzantine aesthetics on the French literature of the Middle Ages. Gautier d’Arras assimilates it, but at the same time modifies its sense. He re-defines the courtly ethos and diminishes the aesthetic character of the motif, typical of the oriental poetics. Precious stones are the contested sign of the East because their beauty is understood as the determinant of Virtue rather than outer beauty. This is a new face of the exotic – not only tamed but also moralised. This modification of the generally accepted hierarchy of values enriches the sapiential, moral and formative aspects of the work.